A multicriteria aware optimal routing approach for enhancing quality of service in device to device communication / Valmik Tilwari - Valmik , Tilwari (2020)
As the world is moving towards the digitalization era, increasing demands of higher data rates, energy effiffifficiency, and seamless connectivity are skyrocketing. Device-to-Device (D2D) communication is one of the key technologies for future Fifth Generation (5G) network. D2D communication technology enhances network coverage, boosts spectral efficiency, has low latency, and enables the devices to communicate with each other, with partial or none involvement of network infrastructure. Therefore, factors of such nature make D2D communication a promising medium guarantying reliability to several telecommunications scenarios. D2D caters to all the needs of it’s users, from the high demand of peer-to-peer users for data transmissions in Ultra-Dense Network (UDN) to building up a network that is resilient against natural disasters. In the orthodox cellular network, all the users are directly connected with a one-hop link to the network infrastructure. In contrast, for the D2D communication, a relay device is needed due to the multi-hop link between source and destination device for data transmission. For this, a routing approach plays a significant role in achieving efficient and reliable data transmission to the end-users. This study proposed three routing approaches in three main D2D communication scenarios. In the conventional D2D communication scenario, the network topology is highly dynamic and changes in an unpredictable manner due to the high displacement of devices in the network. This scenario affected the stability of the network and established routes which significantly degrades the network performance. Therefore, the Mobility, Residual energy, and Link quality Aware Multipath (MRLAM) routing approach is proposed to optimize the network and route stability for the conventional D2D communication scenario. Meanwhile, in the D2D communication UDN scenario, traffic congestion occurs on a single mobile device when there is an excessive flow of packets, and it carries most of the network traffic. This scenario induces data packets transmission end-to-end delay in the network. Therefore, Multipath Battery, Mobility, and Queue length Aware (MBMQA) routing approach is proposed in order to balanced data traffic load among the mobile devices in the D2D communication UDN scenario. Whereas, in the D2D communication-based Disaster Management Scenario (DMS), the mobile devices are equipped with limited energy resources for their vital operation of data transmission. Thus, the connectivity of the devices suffers from packets drops as soon as the device's energy gets exhausted. Similarly, the mobile devices in the network, change their position frequently, which induces the chance of link failure in the established route. Therefore, Energy, Mobility, Backpressure, and Link quality Routing (EMBLR) approach is proposed in the D2D communication based on DMS to balance the energy consumption load among the devices and ensure reliable data transmission. Extensive simulations have been conducted that illustrate that proposed routing approaches significantly enhanced Quality of Service (QoS) network performance metrics for different D2D communication scenarios as compared with other well-known routing approaches. It is evident that the findings presented in the study are useful for designing the routing approach in future D2D communication. Index terms: 5G network, D2D communication; Internet of things; Routing; Multi criteria decision making